Estudio comparativo de la eficacia de dietas suplementarias con daucus carota, cucurbita máxima y bixa orellana y su influencia en parásitos gastrointestinales en la producción de huevos de gallinas ponedoras Lohmann Brown de la granja Toribio Maya del Municipio de Popayán (2022)
The following study had been realized with the purpose to evaluate the effects that can have the maximum Curcubita, the Daucus Carota and The Orellana, when those were implemented on the daily diets on each one of the sheds, to can evaluate the productive behavior and the pigmentation the egg´s bud. To achieve this it has evaluated 40 chickens from the raze Lohmann Brown, of the 38 week to the 49 week, at which have posted in a cubicle, where put on this and distributed 10 birds, those birds where feed with natural dietary supplements giving once a day on adequate rations depending on its adaptability, taking on count that every week its rations it was increased because the progress and adaptability evolution that the chickens presented, to those birds were realized coprological tests to determinate the levels of parasite load levels, and to watch it this increase or decrease, with the supply on those diets. The evaluated variants where, the pigmentation of the egg´s bud, weight and parasite load. The results of this investigation where analyzed with the analysis of the variant ANOVA and the averages where related with the TUKEY method. The averages of production registers founded to the collaboration given by the Rocher hand fan show to us a very significant interaction (p>0.05) which tell us that there aren`t significant between the measures inside the subset 2, with the number of eggs on the first week, this interaction was changing and variant to even the weeks were increasing and the food assimilation also that at the finally of the study it can be observed an interaction highly significant over the egg`s bud pigmentation 17 as the weight. Concluded that the supply on the daily diets were that ones who caused an increase into the weight and the egg`s bud coloration.